Effect of Different Levels of Salinity and Anti-Transpiration on the Growth Characteristics and Chemical Composition of Panicum maximum (Jacq.) - Adel El Wardany; Nasr Elbordiny; Ramadan Abdrabou; Adel Bakr; Yasser Abdelkareem (Arab Universities Journal of Agricultural Sciences, 2022)
This study aimed to determine the effect of different salinity and anti-transpiration levels on the growth and biochemical composition of Panicum maximum plants (Guinea grass) during the spring and summer of 2020. Two different anti-transpiration treatments [molasses (sugarcane) (5 mL/L), kaolin (50 g/L) and control] and three salinity levels (S1 well water as the control and salinity S2 2000 ppm; S3 4000 ppm, S4 6000 ppm) were used in 12 treatments in 72 pots (3 anti-transpiration treatments × 4 salinity treatments × 6 replicates); a randomized complete design was used. Results revealed that the plants achieved the highest plant height (123.77 cm) and dry weight (521.87 g/m2) with kaolin and no salt addition treatment during summer. A higher percentage of proteins and carbohydrates were found in spring than in summer, but there was no significant difference in the salinity levels. A high percentage of ash and fiber contents was also observed during summer, with no significant differences between the anti-transpiration treatments. It could be concluded that P. maximum, as one of the most important fodder crops, could be cultivated in marginal lands, especially during the summer season.